Guarda d´imparentarti con buoni cittadini : a celebração do matrimônio na alta sociedade florentina do Quattrocento - Fallabrino, Maria Verónica Perez (2015)
The purpose of this dissertation is to analyze the celebration of marriage among the high society of Quattrocento Florence, aiming to understand, under a cultural perspective, how marriage was conceived and practiced within the scope of the social relations and the interests of this group. Based upon literary works and personal sources (letters and familiar diaries), we study the matrimonial practices of the rich families of Fifteenth century considering the interest of these families to establish social bonds in order to reinforce the hierarchy and status they held within the society. Thus, based on the ideals spread by humanist literature and experiences recorded by the Florentines themselves, we try to perceive how marriage agreements were established: measuring familiar strategies; the importance of the bonds created from the marriage; the course of the negotiations between the families; the people doing them; and the material, social and moral values that were considered. Once established the several reasons that defined marriages among the high society, we finally focused on the different stages of the marriage process to understand how these moments were celebrated and the meaning and ritual importance of each one of them